The Factors Influencing Investor Intentions to Invest in Equity Crowdfunding in Thailand: A Conceptual Framework - Panitkulpong, Kaimuk; Saengnoree, Amnuay; Deebhijarn, Samart; Teerawatananond, Thapong (My University, 2023)
Equity Crowdfunding (ECF) has emerged as a significant financing tool for early-stage ventures in Thailand, attracting a diverse investor base. Considering the novelty of ECF platforms as non-bank equity investment options, investigating these investors' decisions is essential, even though this is an under-researched area despite ECF's rising popularity. This study aims to identify the key factors influencing investment decisions in ECF and establish a conceptual framework, with a particular focus on projects offering stock issuance through an ECF platform in Thailand. The framework is grounded in the Technology Acceptance Model (TAM3) and incorporates elements from the Information Systems Success Model (ISSM), Innovation Diffusion Theory (IDT), and Social Influence (SI) factors. The intention to invest in an ECF platform serves as the dependent variable within this framework. The research presents a comprehensive model of ECF, intending to provide valuable insights to platform providers and policymakers. This understanding of investor behavior prior to investment could contribute to the growth and sustainability of ECF in Thailand.
Keywords: equity crowdfunding; financial innovation; intention to invest